Links between Gestures and Multisensory Processing: Individual Differences Suggest a Compensation Mechanism - Schmalenbach, Simon B.; Billino, Jutta; Kircher, Tilo; van Kemenade, Bianca M.; Straube, Benjamin (Frontiers in Psychology, 2017)
Speech associated gestures represent an important communication modality. However, individual differ-ences in the production and perception of gestures are not well understood so far. We hypothesized that the perception of multisensory action consequences might play a crucial role. Verbal communication in-volves continuous calibration of audio-visual information produced by the speakers. The effective pro-duction and perception of gestures supporting this process could depend on the given capacities to per-ceive multisensory information accurately. We explored the association between the production and per-ception of gestures and the monitoring of multisensory action consequences in a sample of 31 partici-pants. We applied a recently introduced gesture scale to assess self-reported gesture production and perception in everyday life situations. In the perceptual experiment, we presented unimodal (visual) and bimodal (visual and auditory) sensory outcomes with various delays after a self-initiated (active) or exter-nally generated (passive) button press. Participants had to report whether they detected a delay be-tween the button press and the visual stimulus. We derived psychometric functions for each condition and determined points of subjective equality (PSEs), reflecting detection thresholds for delays. Results support a robust link between gesture scores and detection thresholds. Individuals with higher detection thresholds (lower performance) reported more frequent gesture production and perception and fur-thermore profited more from multisensory information in the experimental task. We propose that our findings indicate a compensational function of multisensory processing as a basis for individual differences in both action outcome monitoring and gesture production and perception in everyday life situations.